AFFECTIVE STRATEGIES USED BY HIGH PROFICIENCY LEARNERS AT HAND FORTUNA CENTER - Anie G Roboh; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2016)
This qualitative study aims to find out the affective strategies used by high proficiency learners at Hand Fortuna Center, Kupang. The theory applied was the theory of Affective Strategies by Oxford (1990) as a main theory and Oxford (2011) as a supporting theory. The source of data was the result of the questionnaires and the transcripts of interview that have been conducted with the ten high proficiency students at Hand Fortuna Center. The findings showed that the learners mostly used the first and the second part of affective strategies, namely “lowering your anxiety” and “encouraging yourself”. There are three sub-strategies in each part such as using “progressive relaxation, deep breathing, or meditation”, “using music”, and “using laughter” (lowering your anxiety) and “making positive statements”, “taking risks wisely”, and “rewarding yourself” (encouraging yourself). The third part of affective strategies, “taking your emotional temperature”, was the least frequently used by the learners. It is possible that the learners might not be familiar with the strategies such as “using a checklist” or “writing a language learning diary”.